Diagnostic Accuracy of ki-67 Labeling Index in Endoscopic Ultrasonography-Fine-Needle Aspiration Cytology and Biopsy of Pancreatic Neuroendocrine Neoplasms - Jung-Soo Pyo; Nae Yu Kim; Kyueng-Whan Min; Il Hwan Oh; Dae Hyun Lim; Byoung Kwan Son (Diagnostics, 2023)
Background: This study aimed to compare the diagnostic accuracy of the Ki-67 labeling index (LI) between endoscopic ultrasonography-fine-needle aspiration cytology/biopsy (EUS-FNAC/FNB) and surgical specimens of pancreatic neuroendocrine neoplasms (PanNENs). Methods: Conventional meta-analysis and diagnostic test accuracy (DTA) reviews were performed on 17 eligible studies. The DTA review involved calculating the sensitivity, specificity, diagnostic odds ratio (OR), and area under the curve (AUC) of the summary receiver operating characteristic (SROC) curve. In addition, subgroup analysis was conducted based on EUS-FNAC and FNB, tumor grade, and tumor size. Results: The overall concordance rate of WHO grade based on Ki-67 LI between the EUS-FNAC/FNB and the surgical specimen was 0.767 (95% confidence interval (CI), 0.713–0.814). Concordance rates of the EUS-FNAC and EUS-FNB subgroups were 0.741 (95% CI, 0.681–0.794) and 0.839 (95% CI, 0.738–0.906), respectively. In the DTA review for grade 3, the sensitivity and specificity were calculated to be 0.786 (95% CI, 0.590–0.917) and 0.998 (95% CI, 0.987–1.000), respectively. The diagnostic OR and AUC of the SROC curve were 150.220 (95% CI, 46.145–489.000) and 0.983, respectively. The sensitivity and specificity were observed to be highest in the grade 1 and 3 subgroups, respectively. Conclusions: Higher concordance of tumor grade based on Ki-67 LI was observed between EUS-FNAC/FNB and surgical specimens, indicating the potential usefulness of Ki-67 LI in predicting PanNEN tumor grade in EUS-FNAC/FNB.